The obstetrician's role in preventing cardiometabolic disease - Hirst, J; Nagraj, S; Franzcog, A; Mackillop, L; Norton, R; Kennedy, S (Wiley, 2019)
Key Content Cardiovascular diseases are the leading causes of death in women and account for the majority of deaths in women living in the UK. Pregnancy is a ‘stress test' for cardiometabolic conditions, identifying women at increased risk during and after pregnancy. Antenatal and postnatal care may therefore be key times for primary and secondary prevention. Given the growing burden of cardiometabolic diseases, pressure is mounting to integrate screening, management and preventative programs into maternity services. Learning Objectives Be familiar with the long‐term consequences that can follow gestational diabetes and hypertensive diseases of pregnancy. Understand the evidence for interventions before and after birth to prevent future morbidity and mortality. Recognise the important role of obstetricians in linking secondary care with primary and preventative care services to prevent cardiovascular and metabolic diseases. Ethical Issues What is the role of the obstetrician in contributing to women's lifelong wellbeing?